Nonrelativistic limit of the abelianized ABJM model and the ADS/CMT correspondence - Lopez-Arcos, Cristhiam; Murugan, Jeff; Nastase, Horatiu [UNESP] (Springer Nature, 2016)
Abstract: We consider the nonrelativistic limit of the abelian reduction of the massive ABJM model proposed in [1], obtaining a supersymmetric version of the Jackiw-Pi model. The system exhibits an N= 2 Super-Schrödinger symmetry with the Jackiw-Pi vortices emerging as BPS solutions. We find that this (2 + 1)-dimensional abelian field theory is dual to a certain (3+1)-dimensional gravity theory that differs somewhat from previously considered abelian condensed matter stand-ins for the ABJM model. We close by commenting on progress in the top-down realization of the AdS/CMT correspondence in a critical string theory.
Keywords: AdS-CFT Correspondence; Holography and condensed matter physics (AdS/CMT); Solitons Monopoles and Instantons; Supersymmetric gauge theory